Investigating Blended Learning Mode in Translation Competence Development - Wenqing Peng; Mu Hu; Peng Bi (SAGE Open, 2023)
There has long been a consensus that translation competence is a multi-componential construct, encompassing linguistic, strategic, and extra-linguistic competence. In this digitalized age, when translators are required to work with complex discourses (e.g., multimodal discourses), the cultivation of translation competence also calls for new insights apart from the traditional face-to-face teaching method. To that end, this study applies the blended learning mode to a translation course so as to enhance students’ translation competence. The application of this blended learning mode is detailed in this article. A quasi-experiment is also carried out to assess the influence of this blended course on the development of participants’ translation competence. Participants’ perceptions of this blended learning mode are also examined. Our results suggest that this blended course improves participants’ translation competence, including their knowledge competence, technological competence, and professional competence. On the whole, participants are satisfied with this learning mode, particularly in terms of the appropriateness, sustainability, and multimodality of the blended course.